Certified School Nurse Perspectives on State‐Mandated Hearing Screens. (August 2016) - Sekhar, Deepa L.; Beiler, Jessica S.; Schaefer, Eric W.; Henning, Antoinette; Dillon, Judith F.; Czarnecki, Beth; Zalewski, Thomas R.
ABSTRACT: BACKGROUND: Approximately 15% of children in the United States 6‐19 years of age have hearing loss. Even mild, unilateral hearing loss may adversely affect educational success. In 2014, the Pennsylvania Department of Health (PA DOH) began updating the 2001 regulations on state‐mandated school hearing screens. To inform the updates, a needs assessment was conducted with PA‐certified school nurses (CSNs) regarding current screening practice and potential barriers to making changes. METHODS: A 42‐item electronic survey of CSNs developed with pediatricians, audiologists, nurses, and the PA DOH was administered in October 2014. RESULTS: There were 536 completed surveys. Most CSNs (50.8%) screened 251‐500 students annually. Only 35.8% strictly followed PA DOH protocol, while 51.6% followed protocol and added nonguideline frequencies. Over half of screens (60.2%) were conducted in places where other people were present. Most CSNs (82.5%) reported annual audiometer calibration, but 92.4% were unsure whether the calibration was exhaustive or limited. Reported barriers to change included time, cost, and staffing. CONCLUSIONS: As most CSNs added frequencies to the PA DOH hearing screen, an update with added frequencies should be well accepted. Clarification regarding test environment and exhaustive audiometer calibration is needed. Adherence to best practice may be optimized by addressing CSN reported barriers to change.